Penyuluhan Rumah Sehat pada Kelompok Karang Taruna di Kabupaten Soppeng - Nur Anny S. Taufieq; Irma Aswani Ahmad (IPTEK: Jurnal Hasil Pengabdian kepada Masyarakat, 2021)
Abstract. Environmental quality is less well marked, with many residents who suffer from diarrhea and tuberculosis. Its caused by citizens' lack of knowledge about the importance of healthy homes and healthy home requirements. Improving the quality of the environment can be done through the role of the youth organization. Problems in community service are still common public knowledge of the importance of the home and the terms of a healthy home. Based on the above problems, the community service aims to increase the general understanding of the importance of healthy homes and healthy home requirements. The method used in the public service increases public knowledge of the importance of healthy homes and healthy home terms; the technique used is lectures, discussion, and debate. The results showed that community service activities increase the importance of healthy homes and healthy home terms, showing that motivation and enthusiasm in participating in these materials are very high. Suggestions for community service are: (1) Keep the same activity in other regions to know the importance of healthy homes and requirements, and (2) Should community service activities be carried out sustainably